2011
DOI: 10.1152/japplphysiol.01402.2010
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to decompression: stress and cytokine gene expression in rat lungs

Abstract: RM. Acclimation to decompression: stress and cytokine gene expression in rat lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Because inflammation has been repeatedly reported after diving, we also assessed whether enalapril treatment could act through its anti-inflammatory action. Previous studies showed that IL-6 is increased with DCS (Ersson et al, 1998 ; Blatteau et al, 2012 ; Bao et al, 2015 ) but not asymptomatic individuals (Chen et al, 2011 ; Blatteau et al, 2012 ). In our study rats treated with enalapril did not have modified levels of this biomarker.…”
Section: Discussionmentioning
confidence: 94%
“…Because inflammation has been repeatedly reported after diving, we also assessed whether enalapril treatment could act through its anti-inflammatory action. Previous studies showed that IL-6 is increased with DCS (Ersson et al, 1998 ; Blatteau et al, 2012 ; Bao et al, 2015 ) but not asymptomatic individuals (Chen et al, 2011 ; Blatteau et al, 2012 ). In our study rats treated with enalapril did not have modified levels of this biomarker.…”
Section: Discussionmentioning
confidence: 94%
“…These results suggested a low-grade balanced activation of proand anti-inflammatory factors. Such activation may protect the circulatory homeostasis during diving; in line with this notion animal studies have indicated that repeated bouts of stressful hyperbaric exposure reduce the risk of morbidity after subsequent exposures (10,34).…”
mentioning
confidence: 87%
“…Since it has been reported that TNF is involved in the progression of DCS, 8,9 we were quite interested in the altered expression of TNF in DCS animals. We further confirmed the elevated expression of TNF in spinal cord tissues of DCS animals from the transcription and protein expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Being a cytokine with various biological actions, TNF-a participates in immune and inflammatory responses. 8,9 TNF exerts its biological activities by binding to its receptor on the cell membrane. After binding, TNF triggers signal transduction pathways, including apoptosis and the nuclear factor kappa-light-chain-enhancer of activated B cells and JNK pathways.…”
Section: Discussionmentioning
confidence: 99%